Understanding online pseudonym usage and its possible effects on platform utility - Chen, Lyndia Yanru (Nanyang Technological University, 2020)
This study posits that the identity online of an individual is made up of an identifier, online perceptions, expectations and behaviour, that will create outcomes or experiences that inform and shape the SNS identity. The username is a prominent feature on SNSs, and the choice of usernames may come from fundamentally different motivations. There is currently limited research to understand online usernames and it is more often viewed as a necessary role of an online identifier. This study aims to show that online usernames are more than an identifier and reveal some common characteristics of the individual. One insight in this study showed that online usernames reflect the individual’s SNS use expectations at the point of account creation. This topic would be an interesting addition to current SNS online user research with regards to username policy, username data analytics, and discovery of user habits and routine based on one’s perceived identity online, that may inform educators and businesses in designing more suitable and engaging learning, transactional or information systems.